Electrostatic Spray Drying of a Milk Protein Matrix—Impact on Maillard Reactions - Doll Chutani; Todor Vasiljevic; Thom Huppertz; Eoin Murphy (Molecules)
Electrostatic spray drying (ESD) of a milk protein matrix comprising whey protein isolate (WPI), skim milk powder (SMP), and lactose was compared to conventional spray drying (CSD) and freeze-drying (FD). ESD and CSD were used to produce powders at low (0.12–0.14), medium (0.16–0.17), and high (0.31–0.36) levels of water activity (aw), while FD powders targeted low aw (0.12). Maillard reaction indicators were studied after drying and during storage for up to 28 days at 20, 40, or 60 °C by measuring free -NH2 groups, as an indicator of available lysine, and 5-hydroxymethylfurfural (HMF). After drying, levels of residual free -NH2 groups were ~15% higher in ESD and FD powders than in their CSD counterparts. CSD powders also had ~14% higher HMF concentrations compared to their ESD and FD counterparts. Storage led to reductions in free -NH2 groups and increases in HMF content in all powders, the extent of which increased with increasing storage temperature. Reductions in free -NH2 groups followed first-order reaction kinetics at 20 and 40 °C but second-order reaction kinetics at 60 °C. Lactose crystallization was detected in high-aw CSD powders after 14 d at 40 °C and in both CSD and ESD powders after 7 d at 60 °C. Overall, we found that ESD is a gentle drying technology which enables production of powders with lower Maillard reaction markers.